Study on the impact of debris flow from tailings dam failure on shale gas well station - Chen, Meibao; Mao, Jingxin; Li, Yang; Jing, Xiaofei (Frontiers in Earth Science, 2023)
The shale gas well station plays a critical role in the extraction of shale gas, and its safety status exerts significant influence not only on shale gas production but also on the ecological balance of the surrounding environment. To investigate the response characteristics of the shale gas well station under the impact of tailings dam failure debris flow, a comprehensive analysis was conducted using a combination of physical modeling and numerical simulation. The analysis focused on the dynamic inundation process and the impact siltation law caused by the downstream flow of tailings dam failure debris at the shale gas well station. The depth of inundation and the extent of siltation damage were employed as key parameters for characterization. Experimental findings revealed that the downstream mudflow inundation process could be divided into three distinct stages: rapid increase (0-60 s), steady increase (60-106 s), and slow advance (106-250 s). The pattern of mudflow siltation height variation at the well station exhibited an initial rise, followed by a subsequent decline and eventual stabilization. The highest siltation volumes recorded at measurement points A to D were 4.4 m, 4 m, 5.2 m, and 6 m, respectively. Additionally, by employing computational fluid dynamics, numerical calculations were performed under unprotected conditions, with the error between the calculated conclusions and the test results not exceeding 15%. Furthermore, the blocking effect of 8 m and 16 m debris flow blocking dam on the debris flow was thoroughly investigated. The study demonstrated that the check dam with a height of 16 m yielded the most effective blockage, resulting in the highest sediment siltation height of 0.4 m. The research results provide some reference for the prevention and control of debris flow disasters.